SISTEMA DE NAVEGAÇÃO POR GEORREFERENCIAMENTO COM CORREÇÃO DE ROTA POR LÓGICA FUZZY APLICADO À ROBÓTICA AGRÍCOLA" - Rosa, Anderson Estevam da (2012)
Precision agriculture is still considered a new topic in Brazil, even by the Brazilian Agricultural Research Corporation (Embrapa), which, in 2012, published a book on the subject and had more than 4.5 million hits in less than a month of its publication. It demonstrates that this is a promising area of interest and can be the difference for Brazil's agriculture be increasingly competitive still in a sustainable way. Thus, the replacement of the manual for an automated process and georeferenced data collection in the field becomes more rapid, standardized, and accurate. One can also observe that the use of mobile devices is perhaps one of the keys to the future, since they are of considerable computational capacity on low cost, and obviously portable. Therefore, this study aims to develop a software for embedded computers or phones, with georeferenced points and routes and route correction using Fuzzy Logic. The correction of the route is necessary due to possible deviations caused by common elements in the field, such as rocks, holes and vegetation. This system will be used by the robot field being developed in the Laboratory of Automation and Robotics at the State University of Ponta Grossa, PR, the AGROBOT. The validation of the computer system was done manually, ie, yet without the robot, the author of this work, performed on foot paths with embedded computer in hand. During the course, the data were collected to study the results, making a comparison between the correction obtained by Fuzzy Logic and mathematics correction given by subtracting the initial and current angle of the device to the target point. As a result it was graphically demonstrated that the use of fuzzy logic has proved more effective in comparison with the simple subtraction mathematics, mainly in response to the error location GPS devices